Impact of income inequality on incone segregation - Yavaş, Mustafa. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
In this study, an agent-based model is built to investigate how income inequality affects income segregation and its characteristics. The model is capable of demonstrating the expected positive relationship between income inequality and income segregation both statistically and visually. In addition, it is found that income inequality conditions the possible levels of income segregation although its positive impact tends to saturate at higher levels. In order to study the characteristics of income segregation, a typology of its profiles is elaborated and the impact of the shape of income inequality on them is studied. It is found that formation or expansion of affluent neighborhoods or gated communities has a positive impact on formation or expansion of ghettos or slums in a city, and vice versa. Furthermore, this study suggests that distribution of economical and status-seeking movements among different segments of population can be interpreted as the material cause of the shape of income segregation profiles. This inquiry is further enriched by focusing on the segregation of the poorest and the richest households that form homogeneous groupings at the extremes of income percentile. Size of the neighborhoods, natural mixing of the households, and housing market inefficiency are discussed as influencers of them.
Keywords: Income distribution.; Income -- Mathematical models.